Performance of Ngawi Police Criminal Investigation Unit Investigations in Disclosing Crimes Aggressive Theft - Akbar, Muhammad; Muchtar, Jarot; Farid, Muhammad Imam (Tanggon Kosala, 2025)
There was a decrease in the percentage of solving theft crimes with aggregation compared to the previous year; in 2021, there were 32 cases, with 25 cases solved or 78.2%; in 2022, there were 38 cases, with 27 cases solved or 71.1%. In 2022, there was a decrease in the percentage of case completion, which was 7.1%. This research used a qualitative study approach because it aligns with the understanding of the qualitative approach above. The research is closely related to a dynamic society, which is poured with descriptive data that can be observed and definite by the reality that occurs in the field. The results of observations made by the author found differences in mechanisms between regulations in perkap and implementation related to reporting. Officers do not immediately make people who come to report a crime to SPKT a Police Report. Only reports that have met two sufficient pieces of evidence will be made a police report by the officer, while reports that have not met two enough pieces of evidence will be made a certificate of receipt of the report. In addition, there are findings related to operational members who do not make Investigation Results Reports, which can hinder the investigation process. The performance of Criminal Investigation Unit investigators in disclosure theft crimes has not been optimally reviewed; it is still found that members who carry out investigation and investigation activities are not according to predetermined laws and procedures.